أثر الالتزام التنظيمي في تحسين جودة الخدمات المصرفية دراسة ميدانية على المصرف المتحدة بالعجيلات (Comprehensive Journal of Science, 2025)
This study aimed to examine the effect of organizational commitment on improving the quality of banking services provided by Al-Mutahid Al-Ajilat Bank from the employees’ perspective. The study adopted the descriptive analytical approach. Primary data were collected through a questionnaire distributed to all employees of the bank, and (21) valid questionnaires were analyzed using SPSS software. The results revealed a high level of organizational commitment among employees and a high level of banking service quality. Statistical analysis also showed a positive and statistically significant effect of organizational commitment on improving banking service quality. This highlights the importance of enhancing organizational commitment as a key approach to improving service performance and strengthening the bank’s competitive position.
Keywords: Organizational Commitment, Banking Service Quality, Al-Mutahid Al-Ajilat Bank.